Right Hemicolectomy and Multivisceral Resection of Right Colon Cancer：A Report of 21 Cases - 赵玉洲 韩广森 鲁朝敏 任莹坤 李剑 马鹏飞 顾炎晖 刘晨宇 王家祥 (Journal of Huazhong University of Science and Technology. Medical sciences, 2015)
The long-and short-term outcomes in 21 patients with right colon cancer after right hemicolectomy and multivisceral resection surgery were investigated. Short-term therapeutic effects and long-term survival rate were retrospectively analyzed in patients with right colon cancer. These individuals underwent right hemicolectomy in combination with multivisceral resections including pancreatic head, duodenum, kidney, liver, gallbladder, and abdominal wall at the Department of General Surgery in the Henan Tumor Hospital between January 2003 and August 2014. The patients had an average age of 58.9 years（range： 39–78）. Three patients had metastatic invasion only to the duodenum; meanwhile 18 patients had invasion to the duodenum and other adjacent organs. The median survival time was 41 months（95% CI： 6.972–75.028） with one death in the perioperative period. No patients lost follow-up. One-, 3-, and 5-year survival rate was 75%, 56%, and 43%, respectively. It was concluded that indications for surgery should be tightly controlled. Favorable clinical outcomes of right hemicolectomy and multivisceral resection surgery were demonstrated for patients with right colon cancer at the T4 stage.